1988
DOI: 10.1007/bf02553745
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-binding protein in human duodenal biopsies

Abstract: Intestinal calcium-binding protein (CaBP) (molecular weight 10,000) was measured by a specific enzyme-linked immunoadsorbent assay in duodenal biopsies of 94 patients (aged 20-89 years). The patients were examined for complaints of upper abdominal dyspepsia, but no significant pathology was found by gastroduodenoscopy. The median amount of CaBP in duodenal biopsies was 6.0 micrograms/mg of cytosolic protein with a coefficient of variation of 0.6. No change in the amount of CaBP per mg of cytosolic protein was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
4
9
1
Order By: Relevance
“…2). The extent of this correlation (r 0´40) is similar to that reported previously for the correlation between 1,25-(OH) 2 D and calcium-binding protein determined by enzyme-linked immunosorbent assay (ELISA) in duodenal biopsies [28].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…2). The extent of this correlation (r 0´40) is similar to that reported previously for the correlation between 1,25-(OH) 2 D and calcium-binding protein determined by enzyme-linked immunosorbent assay (ELISA) in duodenal biopsies [28].…”
Section: Resultssupporting
confidence: 87%
“…In this study we have shown that calbindin-D9k RNA is abundantly expressed in human duodenal biopsies and demonstrated a signi®cant, though weak, positive correlation with circulating 1,25-(OH) 2 D in the population. This links the work of Staun et al [28], who showed a similar degree of correlation of the amounts of expressed calcium binding protein in human duodenum with 1,25-(OH) 2 in the human calbindin-D9k gene. Taken together, these studies imply transcriptional effects of 1,25-(OH) 2 D on calbindin-D9k expression in humans, as in other species.…”
Section: Discussionsupporting
confidence: 85%
“…It is possible that the intestinal mucosal cells are less sensitive to 1 ,25(OH)zD. However, the amount of intestinal Ca binding protein has been reported not to change with age (Staun et al, 1988). Impaired Ca channel function in the elderly may be a possible mechanism since Ca absorption was reported to be reduced in demented patients in the presence of normal levels of vitamin D metabolites (Ferrier et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, some of the antigenic sites did not tolerate the fixing procedures and this may explain why relatively few gold particles were counted. In addition, the amount of human intestinal CaBP shows large variation between individuals (20), a point to be considered when comparing the present study with previous results.…”
Section: Results Discussionmentioning
confidence: 54%